ASEAN regionalism : cooperation, values and institutionalisation - Roberts, Christopher B. (London : Routledge, 2012)
'This book examines the key motivations for and challenges to greater regional integration in Southeast Asia. It covers the full range of issues confronting ASEAN, and discusses both the developments in ASEAN to date and the ones likely to take place in the future.'--Publisher's description.
Includes bibliographical references and index.
Keywords: ASEAN; Regionalism -- Southeast Asia; Southeast Asia -- Foreign relations